1998
DOI: 10.1063/1.121001
|View full text |Cite
|
Sign up to set email alerts
|

Formation of silicon nitride layers by nitrogen ion irradiation of silicon biased to a high voltage in an electron cyclotron resonance microwave plasma

Abstract: Articles you may be interested inEffects of surface oxide layer on nanocavity formation and silver gettering in hydrogen ion implanted silicon

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

1998
1998
2011
2011

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 13 publications
(7 reference statements)
0
2
0
Order By: Relevance
“…Ensinger et al [16] demonstrated that a 25 nm thick silicon nitride layer can be produced on crystalline silicon by exposure to a dense nitrogen plasma produced by an electron cyclotron resonance (ECR) remote plasma source [16]. To achieve the conversion of such a thick layer of crystalline silicon to silicon nitride, a À50 kV bias was applied to the crystalline silicon to raise the nitrogen ion bombardment energy.…”
Section: Introductionmentioning
confidence: 99%
“…Ensinger et al [16] demonstrated that a 25 nm thick silicon nitride layer can be produced on crystalline silicon by exposure to a dense nitrogen plasma produced by an electron cyclotron resonance (ECR) remote plasma source [16]. To achieve the conversion of such a thick layer of crystalline silicon to silicon nitride, a À50 kV bias was applied to the crystalline silicon to raise the nitrogen ion bombardment energy.…”
Section: Introductionmentioning
confidence: 99%
“…13,26 The formation of buried nitride layers has been studied for the high-energy nitrogen ion implantation ͑у50 keV/N ϩ ion͒ of Si. 2,10,24,[27][28][29] Only few articles are published for bombardment using low-energy nitrogen ions ͑0.1-10 keV/ N ϩ ion͒. 2,23,30,31 The ion beam nitridation of Si with N 2 ϩ ions in the 100-1000 eV energy range has been investigated for the near-normal bombardment using predominantly x-ray photoelectron spectroscopy ͑XPS͒.…”
Section: Introductionmentioning
confidence: 99%